2019
DOI: 10.1002/jcb.28902
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and nucleolin influence cell injury, apoptosis and inflammatory factor expression in respiratory syncytial virus‐infected N2a neuronal cells

Abstract: Respiratory syncytial virus (RSV) infection was recently reported to be associated with central nervous system (CNS) symptoms and neurological complications; however, related studies are very limited. Moreover, the molecular mechanism underlying RSV neuropathogenesis is still unclear. Our previous study revealed that toll‐like receptor 4 (TLR4) and nucleolin (C23) could be modulated and that they played a role during RSV infection in mouse neuronal‐2a (N2a) cells. In the present study, the effects of silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…As TLR4 can aggravate inflammatory damage, many studies are based on directly inhibiting TLR4 expression or related signaling pathways to find suitable drugs to protect against the effects of ischemic stroke [ 34 36 ]. There is increasing evidence that down-regulation of TLR4 can significantly inhibit ischemia-induced neuronal apoptosis [ 37 , 38 ]. Besides, TLR4 activation causes the release of IFs such as TNF-a, IL-6, and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…As TLR4 can aggravate inflammatory damage, many studies are based on directly inhibiting TLR4 expression or related signaling pathways to find suitable drugs to protect against the effects of ischemic stroke [ 34 36 ]. There is increasing evidence that down-regulation of TLR4 can significantly inhibit ischemia-induced neuronal apoptosis [ 37 , 38 ]. Besides, TLR4 activation causes the release of IFs such as TNF-a, IL-6, and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…In result, the enhanced immune signalling pathways lead to a stage of hyperresponsiveness to PRRs agonists [ 57 ]. It has been shown that respiratory syncytial virus (RSV)-infected airway epithelial cells become hypersensitive to endotoxin by enhancing TLR4 expression with production of IL-8 and tumor necrosis factor α (TNFα) as well as increased mitogen-activated protein (MAP) kinase activity [ 58 ].…”
Section: Sialic Acids In Covs Infectionsmentioning
confidence: 99%
“…Nucleolin has been identified as part of a multiprotein signaling complex containing annexin A2, calreticulin, and TLR4 on the surface of endothelial cells (34), as well as in complex with heat shock proteins (including HSPA1A), TLR2, and TLR4 on the cell surface of THP-1 cells (35). Further, TLR4 may act as a coreceptor of nucleolin in cellular entry of RSV (36,37). Both nucleolin (18) and TLR4 in conjunction with MD-2 and CD14 (38) have been reported or are known to bind LPS, and engagement of TLR4 can stimulate IL-6 and TNF-α production (39,40).…”
Section: Discussionmentioning
confidence: 99%